Desenvolvimento de procedimento para determinação fotométrica de etanol em bebidas destiladas sem uso de reagentes explorando o efeito Schlieren - Silva, Diogo Santos (2015)
The knowledge and applications of Schlieren effect on the flow injection analysis process (FIA) showed that using the variation of refraction index, formed by concentration gradients during sample dispersion in carrier fluid is a practicable method for ethanol determination in distilled drinks. Based on this effect, we developed an analysis module that performs photometric measurements using flow cells of long optical path length. The method here proposed allowed the determination of ethanol without using reagents. Control of the devices, including solenoid valves and solenoid mini-pumps, was carried out by a microcontroller (Arduino Due) coupled to a microcomputer through serial interface. The control and data acquisition software was written using Visual Basic 6.0, C and C ++ languages. The flow analysis module developed for this study achieved an analytical frequency of 110 samples per hour, sample consumption of 400.2 μL and generation of 2.9 mL of effluent per determination.